Βοοκ Review of "Liquid and Multiple: Individuals and Identities in the Thirteenth-Century Aegean, ed. G. Saint-Guillain, D. Stathakopoulos, Monographies 35, Paris 2012 - ΡΑΓΙΑ Εφη (Byzantina Symmeikta, 2015)
This is a review of the volume "Liquid and Multiple: Individuals and Identities in the Thirteenth-Century Aegean, ed. G. Saint-Guillain, D. Stathakopoulos, Monographies 35, Paris 2012.